Yazilim geliştirme süreçlerinin analizi: Zorluklar, tasarim prensipleri ve tekniksel yaklaşimlar - Alakuş, Talha Burak; Daş, Resul; Türko?lu, Ibrahim (Institute of Electrical and Electronics Engineers Inc., 2017)
The main purpose of this study is to present solution approaches for the challenges during developing software projects. Besides, process models, design principles and technical approaches are submitted through personal experiences. © 2017 IEEE.
2017 International Artificial Intelligence and Data Processing Symposium, IDAP 2017 -- 16 September 2017 through 17 September 2017 -- Malatya -- 115012
Keywords: Challenges; Design principles; Software development process; Standardization activities